Airports as a Strategic Factor of Regional Development in Light of Strategic Regional Programming Documents - Pancer-Cybulska, Ewa; Olipra , Łukasz (Studia Oeconomica Posnaniensia, 2016)
The aim of this article is to answer the question about the role of air transport in the development policy of regions in Poland after accession to the European Union. The authors test the hypothesis that strategic development documents attribute the role of a strategic factor for the development of regions in Poland to airports and wider - the air transport. The basic research method used in the study is the analysis of the main regional policy programming documents, i.e. the voivodship’s development strategies and regional operational programs (ROP) in force in the financial perspectives 2007-2013 and 2014-2020. Literature studies and desk research have also been carried out. Analysis of the documents allows the conclusion that the actions of the regional authorities were mainly complementary to the government’s program. But it is worth noting that thanks to the efforts of regional authorities, the airport infrastructure in Poland has been successfully completed by two new airports: Lublin Swidnik and Warsaw-Modlin. Based on the analysis of regional policy programming documents, the above hypothesis can be positively verified. In most cases, regional authorities support the development of air transport infrastructure in the regions or declare their willingness to support it. It should be noted, however, that actions and initiatives taken by regional authorities arise more from political reasons than from reliable economic analysis. Therefore, there is a need for research and analysis on the economic factors, efficiency, and rationality of regional initiatives to invest in the development of airport infrastructure in Poland.